pH Indicator Paper by Immobilizing Turmeric Rhizome Ethanol Extract on Filter Paper - Maria Aloisia Uron Leba; Maria Benedikta Tukan; Faderina Komisia (JURNAL SAINS NATURAL, 2022)
Research has been carried out on the manufacture of pH indicator paper by immobilizing turmeric rhizome ethanol extract on filter paper. Turmeric extract was extracted from turmeric rhizome samples with 95% medical-grade ethanol and 96% analytical grade ethanol. The ethanol extract obtained was immobilized by adsorption on filter paper. This research aimed to examine the phytochemicals of turmeric ethanol extract, the effectiveness of turmeric ethanol extract on pH solution of 1 -14, the effectiveness of turmeric paper on pH solution of 1-14, colour stability and effectiveness of turmeric paper based on storage time. Based on the research results obtained, EEK-95% and EEK-96% contain alkaloids, flavonoids, tannins and triterpenoids, EEK-95% and EEK-96% are yellow at pH 1-7, yellow-orange at pH 7.5-7.7, pale brick red at pH 7.8-8 and brick red at pH 9-14, KIK-95% and KIK-96% are yellow at pH 1-7.5, brick red at pH 7.6-9 and dark brick red at pH 10-14, KIK-95% and KIK-96% are stable for more than 5 months and still give a good response.Keywords: curcumin; turmeric; pH indicator; indicator paper; natural indicatorABSTRAKKertas Indikator pH dengan Mengimmobilisasikan Ekstrak Etanol Rimpang Kunyit pada Kertas SaringTelah dilakukan penelitian pembuatan kertas indikator pH dengan mengimmobilisasikan ekstrak etanol rimpang kunyit pada kertas saring. Ekstrak kunyit diekstraksi dari sampel rimpang kunyit dengan pelarut etanol 95 % grade medis dan etanol 96% grade analisis. Ekstrak etanol yang diperoleh diimobilisasikan secara adsorbsi pada kertas saring. Tujuan dari penelitian ini untuk mengkaji kandungan  fitokimia ekstrak etanol kunyit, efektivitas ekstrak etanol kunyit pada larutan pH 1 -14, efektivitas kertas kunyit pada larutan pH 1-14, stabilitas warna dan efektivitas kertas kunyit berdasarkan waktu penyimpanan. Berdasarkan hasil penelitian diperoleh EEK-95% dan EEK-96% mengandung alkaloid, flavonoid, tanin dan triterpenoid, EEK-95% dan EEK-96% berwarna kuning pada pH 1-7, kuning oranye pada pH 7,5-7,7, merah bata pudar pada pH 7,8-8 dan merah bata pada pH 9-14,  KIK-95% dan KIK-96% berwarna kuning pada pH 1-7,5, merah bata pada pH 7,6-9 dan merah bata pekat pada pH 10-14, KIK-95% dan KIK-96% stabil hingga lebih dari 5 bulan dan masih memberikan respon yang baik.Kata kunci: kurkumin; kunyit; indikator pH; kertas indikator; indikator alami